Quantifying Charge‐Carrier Mobilities and Recombination Rates in Metal Halide Perovskites from Time‐Resolved Microwave Photoconductivity Measurements. Issue 26 (5th February 2020) - Savenije, Tom J.; Guo, Dengyang; Caselli, Valentina M.; Hutter, Eline M.
Abstract: The unprecedented rise in the power conversion efficiency of solar cells based on metal halide perovskites (MHPs) has led to enormous research effort to understand their photophysical properties. The progress made in understanding the mobility and recombination of photogenerated charge carriers from nanosecond to microsecond time scales, monitored using electrodeless transient photoconductivity techniques, is reviewed. In addition, a kinetic model to obtain rate constants from transient data recorded using a wide range of laser intensities is presented. For various MHPs the temperature dependence of the mobilities and recombination rates are evaluated. Furthermore, it is shown how these rate constants can be used to predict the upper limit for the open‐circuit voltage V oc of the corresponding device. Finally, the photophysical properties of MHPs that are not yet fully understood are explored, and recommendations for future research directions are made. Abstract : Progress in understanding the mobility and recombination of photoinduced charge carriers in metal halide perovskites (MHPs) is reviewed. Using a kinetic model to analyze microwave conductance transients, the mobilities and recombination rates including their temperature dependence for various MHPs are evaluated. Furthermore, it is shown how these rate constants can be used to predict steady‐state parameters of corresponding devices.